1966
DOI: 10.1177/00220345660450022401
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries Incidence in North and South Dakota Indian School Children during 30 Years

Abstract: SYNOPSIS IN INTERLINGUA INCIDENTIA DE CARIE DENTAL DURANTE TRENTA ANNOS IN SCHOLARES INDIAN DE NORD- E SUD-DAKOTA.-Un total de 6988 examines dental esseva effectuate in juveniles sioux visitante octo internatos de Nord- e Sud-Dakota durante le periodo ab 1959 ad 1962. Esseva effectuate comparationes con datos de prevalentia de carie dental a base de examines de 926 juveniles sioux in le mesme reservationes durante le periodo ab 1929 ad 1932. Le methodos initialmente reportate esseva observate subsequentemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The same clinical examination techniques were used in the two studies to designate decayed, missing or filled teeth (DMFT) in the permanent dentition; comparisons for the youngest age group (under age 8) showed a tripling of DMFT (0.45 in 1932 and 1.76 in 1961) with a 1.31 DMFT increase between the two time points (Ship, 1966). Ship (1966) speculated that while dietary/nutritional changes, abnormalities in dental structure, or changes in fluoride exposure may explain some of the increase in caries prevalence, a longitudinal study would be necessary to understand the etiologic reasons for the changes observed. Jones and Phipps (1992) (Jones and Phipps, 1992).…”
Section: Dental Caries In Native American Childrenmentioning
confidence: 99%
“…The same clinical examination techniques were used in the two studies to designate decayed, missing or filled teeth (DMFT) in the permanent dentition; comparisons for the youngest age group (under age 8) showed a tripling of DMFT (0.45 in 1932 and 1.76 in 1961) with a 1.31 DMFT increase between the two time points (Ship, 1966). Ship (1966) speculated that while dietary/nutritional changes, abnormalities in dental structure, or changes in fluoride exposure may explain some of the increase in caries prevalence, a longitudinal study would be necessary to understand the etiologic reasons for the changes observed. Jones and Phipps (1992) (Jones and Phipps, 1992).…”
Section: Dental Caries In Native American Childrenmentioning
confidence: 99%